CETP inhibitor evacetrapib enters mouse brain tissue - Phénix, Jasmine; Côté, Jonathan; Dieme, Denis; Recinto, Sherilyn J.; Oestereich, Felix; Efrem, Sasen; Haddad, Sami; Bouchard, Michèle; Munter, Lisa Marie (Frontiers in Pharmacology, 2023)
High levels of plasma cholesterol, especially high levels of low-density lipoprotein cholesterol (LDL-C), have been associated with an increased risk of Alzheimer’s disease. The cholesteryl ester transfer protein (CETP) in plasma distributes cholesteryl esters between lipoproteins and increases LDL-C in plasma. Epidemiologically, decreased CETP activity has been associated with sustained cognitive performance during aging, longevity, and a lower risk of Alzheimer’s disease. Thus, pharmacological CETP inhibitors could be repurposed for the treatment of Alzheimer’s disease as they are safe and effective at lowering CETP activity and LDL-C. Although CETP is mostly expressed by the liver and secreted into the bloodstream, it is also expressed by astrocytes in the brain. Therefore, it is important to determine whether CETP inhibitors can enter the brain. Here, we describe the pharmacokinetic parameters of the CETP inhibitor evacetrapib in the plasma, liver, and brain tissues of CETP transgenic mice. We show that evacetrapib crosses the blood–brain barrier and is detectable in brain tissue 0.5 h after a 40 mg/kg i.v. injection in a non-linear function. We conclude that evacetrapib may prove to be a good candidate to treat CETP-mediated cholesterol dysregulation in Alzheimer’s disease.